Cranberries versus lingonberries: A challenging authentication of similar Vaccinium fruit. (30th June 2019) - Hurkova, Kamila; Uttl, Leos; Rubert, Josep; Navratilova, Klara; Kocourek, Vladimir; Stranska-Zachariasova, Milena; Paprstein, Frantisek; Hajslova, Jana
Highlights: Metabolomic fingerprinting was employed for berries classification. Biomarkers differentiating lingonberries and cranberries were identified. The addition of cranberries to lingonberries can be discovered down to 1% ( w/w ). Influence of drying process on berries metabolome was assessed. Abstract: Due to unique phytochemicals contained, Vaccinum berries are known to have a number of positive health effects. In this context, lingonberries ( Vaccinium vitis-idaea ) are considered to be the most effective, thus finding many uses. Recently, fraud suspicion on lingonberries-based products has been reported, partial or even total replacement by less valued cranberries ( Vaccinium macrocarpon ) was found. In this study, metabolomic fingerprinting employing instrumental platform consisting of U-HPLC-HRMS/MS was investigated for discrimination between the two Vaccinum berries species. Methanolic extracts of 33 authentic samples from two harvest years were analyzed and chemometric evaluation was performed to identify significant marker compounds, their stability during drying process was assessed, too. The characteristic markers most contributing to berries classification were representatives of polyphenols and phospholipids. Peonidin 3-O-arabinoside and myricetin 3-O-glucoside, not occurring in lingonberries, enabled to discover the presence of cranberries in prepared admixtures down to 1% ( w/w ).